Bilateral internal thoracic arteries: what is the State of the ART?. (September 2017) - Yanagawa, Bobby; Verma, Subodh; Puskas, John D.
Abstract : Purpose of review: To provide a broad overview of the current state of knowledge of coronary artery bypass grafting with bilateral internal thoracic artery (BITA). Recent findings: There exists a large body of literature from mostly observational studies supporting the use of BITA in patients undergoing coronary artery bypass grafting but selection bias is a major issue with nonrandomized data. The precise method of BITA use does not appear to impact graft patency nor clinical outcomes – in other words, BITA in any configuration appears to be protective. The major downside is the increased risk of sternal complications, which can be mitigated with sternal-sparring adjuncts. The 5-year interim results of the landmark Arterial Revascularization Trial comparing BITA versus single internal thoracic artery did not show a clinical benefit for BITA but the end-of-trial results are pending. Despite wide guideline support for BITA use, uptake in the surgical community remains low and this is likely because of technical and institutional barriers. Summary: The published literature thus far supports surgical revascularization with BITA and we eagerly await the 10-year Arterial Revascularization Trial results. The general consensus is that a greater proportion of surgical revascularization should be performed using BITA.